Effect of heating on the anthocyanin and iron content of black rice (Oryza sativa) - Quenga, Erwin Chris Delizo (2011.)
Blach rice (Oryza sativa) is valued for its high anthocyanin and iron content.
Sotech thesis.
Keywords: Black rice; Oryza sativa; Anthocyanin; Iron